The group interview [ (Video Education Australasia, 2004)
The group interview is becoming an increasingly common form of first interview for a range of positions. In this program we see how retail giant Coles Myer and leading accounting firm Pricewaterhouse Coopers conduct their group interviews and hear from their recruitment experts, providing students with valuable insight into how a group interview is run and pointers on how to perform well in such an interview.